The Influence of Service Quality and Price on Customer Satisfaction of GoFood on the Gojek Application among University Students in Pontianak City - Afriana Afriana; Fenni Supriadi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the effect of service quality and price on customer satisfaction of the GoFood service on the Gojek application among university students in Pontianak City. This research employs a quantitative approach using an associative method. The study involved a sample of 100 respondents selected through purposive sampling. The instrument testing techniques used in this research include validity tests, reliability tests, classical assumption tests (normality test, linearity test, and multicollinearity test), and hypothesis testing which consists of multiple linear regression analysis, correlation coefficient test, coefficient of determination test, simultaneous test (F-test), and partial test (t-test). Based on the results of the multiple linear regression analysis, the regression equation is obtained as follows: Y = 1.042 + 0.438 X₁ + 0.254 X₂. The correlation coefficient result is 0.738, indicating that the relationship between service quality and price variables on customer satisfaction falls into the strong category. The coefficient of determination shows a value of 0.544, meaning that 54.4% of customer satisfaction is influenced by service quality and price, while the remaining 45.6% is influenced by other variables not examined in this study. The results of the simultaneous test indicate that both service quality and price variables simultaneously have a significant effect on customer satisfaction of GoFood users on the Gojek application among university students in Pontianak City. The partial test results show that service quality has a positive and significant effect on customer satisfaction, and the price variable also has a positive and significant effect on the customer satisfaction of GoFood users on the Gojek application among university students in Pontianak City.